2006
DOI: 10.1038/sj.eye.6702242
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile ocular blood flow in asymmetric age-related macular degeneration

Abstract: Purpose Ocular perfusion abnormalities have been proposed in the pathogenesis of age-related macular degeneration (AMD) with differences in pulsatile ocular blood flow (POBF) in eyes with asymmetric AMD in Japanese and Taiwanese patients. The purpose of our study was to observe POBF difference in the fellow eyes of Caucasians with asymmetric AMD. Methods This was a cross-sectional study comparing POBF in three groups of patients with asymmetric AMD in the fellow eyes: Group 1 (n ¼ 21) with drusen and active ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…In this study, we performed monthly ranibizumab injections consecutively three times. It was reported that optimal timing for ranibizumab injections for wet-type AMD is the first 3 months, and it was suggested to inject ranibizumab There are some reports about the ocular blood flow in wet-type AMD in the literature [17][18][19]. Chen et al reported that the pulsatile ocular blood flow (POBF) was significantly higher in eyes with CNV than the contralateral eyes with drusen, but Mori et al found the opposite [7,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we performed monthly ranibizumab injections consecutively three times. It was reported that optimal timing for ranibizumab injections for wet-type AMD is the first 3 months, and it was suggested to inject ranibizumab There are some reports about the ocular blood flow in wet-type AMD in the literature [17][18][19]. Chen et al reported that the pulsatile ocular blood flow (POBF) was significantly higher in eyes with CNV than the contralateral eyes with drusen, but Mori et al found the opposite [7,17].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported that the pulsatile ocular blood flow (POBF) was significantly higher in eyes with CNV than the contralateral eyes with drusen, but Mori et al found the opposite [7,17]. On the other hand, Sandhu et al revealed that POBF was not different between fellow eyes of patients with asymmetric AMD [18]. But it seems more logical that the reduced blood flow in the choroid is associated with the development and progression of wet-type AMD [19].…”
Section: Discussionmentioning
confidence: 99%
“…[94][95][96] On the other hand, no difference was found between POBF levels in the 2 eyes of patients with asymmetric AMD in a Caucasian population. 97 Using laser interferometric measurement of fundus pulsation amplitude, we have shown that the heartbeat-related distance change between the cornea and retina is selectively reduced at the membrane in patients with CNV. 98 In recent years, some studies have also investigated retinal blood flow in AMD.…”
Section: Degenerationmentioning
confidence: 94%
“…107,108 A few studies have indicated that POBF is reduced in patients with AMD compared to healthy controls; [109][110] however, no difference was found in POBF between the two eyes of Caucasian patients with asymmetric AMD. 111 Studies have also investigated retinal blood fl ow in AMD. Applying the laser Doppler technique to retinal arteries, pulsatility was found to increase with severity of AMD; however, despite an increase in pulsatility, retinal blood fl ow remained constant, indicating reduced vascular compliance proximal to the eye.…”
Section: Ocular Blood Fl Ow and Age-related Macular Degenerationmentioning
confidence: 99%